Kontekstualisasi Makna Ukhuwwah Islâmîyah Perspektif Jemaah Tarekat Shatarîyah di Nganjuk Jawa Timur - Warsito Warsito (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2015)
This article discusses the symbols, process, and meaning of ukhuwwa Islâmiyya (Islamic brotherhood) within the perspective of the followers of the Tarekat Shatârîyah in Tanjunganom Nganjuk East Java. The research results indicate that the making process of ukhuwwa Islâmiyya has been initiated through bay’ah towards murshid (Guru Wasîtah). To the followers of the Tarekat Shatarîyah, murshid is a person who becomes the main symbol that unites them. The intensity of interaction and meetings have also played a significant role in the creation process of ukhuwwah islâmîyah among the adherents the Tarekat. When they gather, they perform several rituals such as performing qiyâm al-layl and dhikr and reciting what so-called muji wali kutub. They also discuss various problems of religious and social issues. The making process of ukhuwwa Islâmiyya is also convoyed with the use and carrying out of certain symbol and ritual such as wearing the Malakîyah ring and reciting Asmâ’ 9. To the followers of this Tarekat, ukhuwwa Islâmiyya means a brotherhood which is founded merely on the spirit of pure intention without any inclination to gain worldly benefits. To them, it is a relation that is established based on obedience upon Guru Wasîtah to create an eternal brotherhood for the sake of God regardless of their social status.